2020
DOI: 10.1016/j.jssr.2020.01.002
|View full text |Cite
|
Sign up to set email alerts
|

A global perspective? Framing analysis of U.S. textbooks’ discussion of Nigeria

Abstract: Students are expected to develop the intellectual capacity needed to accurately portray other world societies. Few research studies in social studies education, however, draw on a systematic textbook analysis to investigate global perspectives on non-Western societies such as those found in African nations. Situated in framing theory, this study employs a qualitative content analysis approach to examine textual and visual curricular representations of non-Western societies framed in the content of four U.S. wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…This included viewing the world as divided and learning about saving the environment according to individualistic and anthropocentric meaning perspectives. While earlier research shown Westerncentrism in teaching material (Ajagán-Lester, 2000;Kamali, 2006;Marmer et al, 2010;Mikander, 2015;Odebiyi & Sunal, 2020;Wilinsky, 1998) and highlighted teacher-candidates' Western-centric beliefs (Hannah, 2017), the present study has shown how such meaning perspectives are perpetuated in on-going teaching practice. The teacher's way of asking questions (Mehan, 1979;Sinclair & Coulthard, 1975) and using evaluative resources of language (Martin & White, 2005;Walldén, 2020b) was key in pointing out and reinforcing these meaning perspectives.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…This included viewing the world as divided and learning about saving the environment according to individualistic and anthropocentric meaning perspectives. While earlier research shown Westerncentrism in teaching material (Ajagán-Lester, 2000;Kamali, 2006;Marmer et al, 2010;Mikander, 2015;Odebiyi & Sunal, 2020;Wilinsky, 1998) and highlighted teacher-candidates' Western-centric beliefs (Hannah, 2017), the present study has shown how such meaning perspectives are perpetuated in on-going teaching practice. The teacher's way of asking questions (Mehan, 1979;Sinclair & Coulthard, 1975) and using evaluative resources of language (Martin & White, 2005;Walldén, 2020b) was key in pointing out and reinforcing these meaning perspectives.…”
Section: Discussioncontrasting
confidence: 72%
“…In relation to the teaching of social studies in Nordic countries, textbook analyses have highlighted the transmission of Western-centric perspectives (Ajagán-Lester, 2000;Kamali, 2006;Mikander, 2015). Deficit perspectives on life in non-Western countries have also been noted in international research on social studies textbooks (e.g., Marmer et al, 2010;Odebiyi & Sunal, 2020). In analyses of civics textbook material relating to issues of climate change, Ideland (2019) has shown that the perspective of environmental sustainability is shaped by neoliberalism, as a matter of exercising consumer power (see also Lloro-Bidart, 2017).…”
Section: Introductionmentioning
confidence: 96%
“…A goal of reform is to help students develop meanings that align with the capacity for social responsibility, as the quest for informed action requires students to critically consider civic discourses based on the understanding of real-life issues (Swan & Griffin, 2013). Social studies education, with the curricular-instructional goal of informed action, challenges students to methodically consider how social issues are constructed, how they are experienced or ignored by different groups and how they are sustained, as well as take steps to address the social issues of concern (Levinson et al, 2013; NCSS, 2013; Odebiyi & Sunal, 2020b; Sunal & Haas, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Benchmarks are standards’ learning objectives representing the expected competencies young learners must demonstrate after they have been exposed to the content of the standards. Social studies scholars have argued that since content standards are a state's stance on social studies, they should focus on framing critical thinking in real-life contexts (Busey & Walker, 2017; Eargle, 2016; Levstik & Tyson, 2008; Odebiyi & Sunal, 2020a; Sunal & Haas, 2011). That is, the thinking promoted by state content standards should be critical and situated in contexts transcending “blind allegiance to the state or a belief in ideals of liberal democracy” (Busey et al, p. 456).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of studies in the field of textbook analysis has been investigating cultural values in textbooks (Almujaiwel, 2018;Huang, 2019;Odebiyi & Sunal, 2020;Toledo-Sandoval, 2020;Uzum, et al 2021). For instance, Almujaiwel (2018) reported a corpus-based analysis study to find the cultural elements portrayed in the Saudi education EFL textbooks.…”
Section: Introductionmentioning
confidence: 99%